Keeping Food Safe: Shopping and Transporting Foods - Claudia Peñuela; Amarat Simonne (EDIS, 2012)
Grocery shopping can be an entertaining activity, but effective shopping involves lots of planning and organization, depending on individual needs and choices in different grocery stores. Good planning and organization can save money and time. Have you ever wondered if you follow safe food handling practices when you buy and transport food? Follow the key guidelines in this 2-page fact sheet to protect yourself and your family! Written by Claudia Peñuela and Amarat Simonne, and published by the UF Department of Family, Youth and Community Sciences, March 2012. Reviewed July 2015.